Sunday, 18 March 2012

How RI = (ROE - r) x B0?

It is a simple derivation.

RI1 = NI1- rB0

NI = ROE x B0

RI1 = ROExB0 - rB0
RI1 = B0 (ROE - r)
RI1 = (ROE - r) B0

1 comment:

  1. I've been exploring for a bit for any high-quality articles
    or weblog posts in this kind of area . Exploring in Yahoo I at
    last stumbled upon this website. Studying this info So i'm
    satisfied to exhibit that I've a very excellent uncanny feeling I discovered
    exactly what I needed. I such a lot certainly will make sure to do not omit this
    web site and provides it a glance regularly.

    Review my web blog: haarausfall stress reversibel